Analisis Faktor-Faktor yang Mempengaruhi Loading Steel Plate dan Coils di Pelabuhan Cigading - Riyadi, Slamet; Pratama, Robby (Politeknik Pelayaran Sumatera Barat, 2025)
This study analyzes the factors that influence the loading process of steel plates and coils at Cigading Port, Cilegon, Banten, which serves as a specialized terminal for the steel industry. Steel cargoes, due to their heavy weight and large dimensions, require specific handling facilities, reliable equipment, and skilled manpower to ensure operational efficiency and cargo safety. Using a qualitative descriptive approach, data were collected through field observations, in-depth interviews with port operators, and document analysis. The findings indicate that both internal factors—such as cargo conditions, equipment availability, labor skills, and stowage planning accuracy—and external factors, including weather conditions, port facility limitations, and high vessel traffic, significantly affect loading performance. Specific issues identified include waiting for dunnage, crane malfunctions, and hatch cover closures due to rain, which increase vessel waiting time and logistics costs. On the other hand, operational practices such as non-stop working can enhance efficiency and reduce delays when supported by adequate resources and safety measures. The study concludes that optimizing cargo handling at Cigading Port requires integrated management involving port authorities, shipping agents, steel industries, and logistics companies. Recommendations highlight the need for improved planning, real-time weather monitoring, preventive equipment maintenance, and stronger stakeholder coordination to minimize delays and support the smooth distribution of steel across Indonesia.